2003
DOI: 10.1115/1.1614817
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Flow in Mechanical Heart Valves: Grid Resolution and the Assumption of Flow Symmetry

Abstract: A numerical method is developed for simulating unsteady, 3-D, laminar flow through a bileaflet mechanical heart valve with the leaflets fixed. The method employs a dual-time-stepping artificial-compressibility approach together with overset (Chimera) grids and is second-order accurate in space and time. Calculations are carried out for the full 3-D valve geometry under steady inflow conditions on meshes with a total number of nodes ranging from 4 x 10(5) to 1.6 x 10(6). The computed results show that downstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
5

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 23 publications
4
56
0
5
Order By: Relevance
“…Similar axisymmetric designs have been used in previous studies and have been shown to reproduce primary flow structures of interest such as strong jet shear layers, and sinus flow recirculation relevant in the clinical setting [5,9,10]. The design, however, does not account for flow complexities associated with flow in three sinuses of Valsalva, or distensible aortic walls.…”
Section: Flow Loop and Test Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar axisymmetric designs have been used in previous studies and have been shown to reproduce primary flow structures of interest such as strong jet shear layers, and sinus flow recirculation relevant in the clinical setting [5,9,10]. The design, however, does not account for flow complexities associated with flow in three sinuses of Valsalva, or distensible aortic walls.…”
Section: Flow Loop and Test Sectionmentioning
confidence: 99%
“…In a low Reynolds number CFD simulation, Ge et al [10] found symmetry breaking about the XY plane at Re = 750. It is therefore likely that there was some degree of asymmetry about the XY plane in the current study (where Re = 7600).…”
Section: D Flow Structurementioning
confidence: 99%
“…The aortic sinus geometry was axisymmetric which has proved useful in CFD validation studies (Ge et al 2003, Dasi et al 2007, Shahbazi 2007. The sinus profile was a b-spline curve generated by Solid Edge V18 and defined by the points given in Table 2 …”
Section: Aortic Sinus Sectionmentioning
confidence: 99%
“…Ge and Sotiropolus (Ge et al, 2003) were the first to successfully use direct numerical simulations of pulsatile flow through bileaftet mechanical heart valves (BHMV). They simulated blood flow through a BHMV embedded within a straight aortic segment using an IBM approach, and they conducted in vitro studies using a similar experimental set-up.…”
Section: Initial Algorithmic Methods Included the Eulerian And Lagranmentioning
confidence: 99%
“…We summarize some important milestones in CFD of heart valves and heart valve prostheses here: The flow through a tilting disk in a permanently half open position was simulated using a FEM approach by Shim and Cham (Shim and Chang, 1994). Ge et al (Ge et al, 2005;Ge et al, 2003) performed equations that also accounted for turbulence. King et al (King et al, 1996) described the presence of orifice jets during systole velocities in a CarboMedics® valve.…”
Section: In Heart Valve Studiesmentioning
confidence: 99%